The Guaranty Trust Bank of Nigeria: From niche positioning to mass-market branding - Maklan, Stan; Knox, Simon; Michel, Stefan (John Wiley & Sons, Ltd, 2009)
This case describes a strategic marketing dilemma facing Tayo Aderinokun, the cofounder and managing director (CEO) of the highly successful Guaranty Trust Bank (GTBank) of Nigeria. In its initial 15 years, GTBank has grown dramatically to become the most respected corporate bank in Nigeria, renowned for both its professionalism and high ethical standards. However, the environment is changing dramatically, and the bank needs to grow quickly in order to survive: perhaps doubling or tripling its size in the next five years. Aderinokun has ruled out merger or acquisition in the immediate future, so organic growth is the only way forward. There is insufficient room for growth in its current commercial niche, so GTBank has decided that the emerging Nigerian retail banking sector is its growth pathway. However, there are big challenges: GTBank's brand, marketing mix, people, and operating methods are finely tuned for corporate banking, and it is not immediately obvious how it will leverage its assets to compete in the emerging retail banking market. In addition, competitors are attacking GTBank in its core corporate segment. The case explores a classic strategic marketing dilemma: when is a highly successful niche brand forced to abandon its unique selling point and go for growth in the mainstream market? How does it leverage that which makes it special so that it offers some compelling advantage for its new customers? Can the niche brand execute well on a large scale? How does it embed its values and behaviors in a new context? Does it have the money, people, culture, and ambition to take share from established competitors in the new market segments? Will its expansion plans make its core business more vulnerable to competitors? The case explores the strategic context using the established marketing planning tools of political/legal, economic, sociocultural, technological, and environmental (PESTE) and strengths, weaknesses, opportunities, and threats (SWOT) analyses, and features advertising themes the bank has developed for mass-market communication purposes to illustrate the far- reaching implications of the expansion of its retail business.